Knowledge and Attitudes of Parents with Prevalence of Autism in Children in Schools with Special Needs (SABK) Unggul Sakti Jambi City - Hendry Boy; Rina Kurnianti; Satria Al Fatiha (Jurnal Kesehatan Gigi, 2019)
Oral and dental health is important for anyone, including children with special needs. According to the Ministry of Health of the Republic of Indonesia, the role of parents, especially mothers, is very important in maintaining the cleanliness of their child's teeth and mouth. Especially in autistic children, caries and gingivitis are encountered, and while their behavior will cause dental care to be rather difficult. Dental caries is a dental tissue disease characterized by tissue damage, starting from the surface of the tooth extending towards the pulp. The study was to determine the relationship of knowledge and attitudes of parents with the prevalence of dental caries in autistic children in the School of Children with Special Needs of Jambi City. This study used a cross sectional approach. The sampling technique used was purposive sampling as many as 30 respondents. The measuring instruments used were questionnaires and dental caries observation sheets. Prevalence of dental caries was 77% or 23 children had caries, knowledge of parents of autistic children was 86.7% or 26 people had high criteria while those with moderate criteria were 13.3% or 4 people and attitudes in parents of autistic children were as much as 76.7% or 23 people have good criteria while those that have good criteria are 23.3% or 7 people. There is relationship between the level of knowledge of parents with the prevalence of dental caries in autistic children (p value = 0.031) and OR = 16.5 and there is relationship between attitudes of parents with the prevalence of dental caries (p value = 0.033), and OR = 8.88. There is a significant relationship between the level of knowledge of parents with the prevalence of dental caries in autistic children and there is a significant relationship between attitudes of parents with the prevalence of dental caries.